Research in Pedagogical Aspects of The Axiological Approach in Improving Students' Legal Culture - Rakhmatullayeva Gulnozakhan Mavlanjonovna (American Journal Of Social Sciences And Humanity Research, 2026)
This in the article students legal culture in promotion axiological approach pedagogical the essence of it theoretical basics and practical mechanisms systematic accordingly research The research relevance globalization, digital transformation and citizenship society development under the circumstances of the youth legal consciousness, legal culture and social responsibility formation necessity with is determined. In the article axiology – values about doctrine as pedagogical in process person's legal values, morals principles, citizenship position and legal behavior of formation methodological basis as interpretation Research to the results according to, axiological approach based on organization done education process in students law priority, social justice, legal responsibility and human to the rights respect such as values stable shapes.